(untitled) - Robbins, Stephen P. (Upper Saddle River, N.J., 2000)
Essentials of Organizational Behavior, Sixth Edition provides a reality-based review of organizational behavior in an abbreviated format. Stephen P. Robbins integrates timely topics throughout the book, such as diversity, globalization, and ethics
Keywords: Organizational behavior,Hành vi tổ chức